Contemporary Paradigm of Sustainable Development in the European Union - Almeida, Fernando; Amoedo, Nelson (International Journal of Management and Sustainability, 2020)
This study aims to explore the level of sustainable development in the European Union and examines the relationship that may exist between the sustainability index and the population of its member states, the GDP per capita, and the investments made in R&D. Furthermore, it aims to explore the role of the geographical region as a determining factor in the performance of these countries in each sustainability dimension. The research methodology employs a quantitative approach supported by the adoption of simple and multiple linear regression, cluster analysis, and variance analysis (ANOVA). The findings reveal that R&D expenditure is mainly a determining factor in a country’s sustainable performance. Moreover, it has been possible to identify several asymmetries, with geographical region emerging as a determining factor in the performance of European Union countries in 11 of the 17 dimensions of sustainability. This work offers both theoretical and practical contributions. From the theoretical perspective, it explores the relationship between sustainability and investments in R&D, GDP per capita, and population. From a practical point of view, it offers relevant information to be used by European Union countries to establish supportive policies to enhance the sustainability of economic growth.